PROFIL PERTUMBUHAN KAMBING PERANAKAN ETAWAH PADA PETERNAKAN RAKYAT DI KAMPUNG BUGIS DESA SERANGAN DENPASAR BALI - FRANGESTU S.; L. DOLOKSARIBU; A. A. OKA (Majalah Ilmiah Peternakan, 2021)
The purpose of this study was to identify body dimensions that influenced the growth of goats reared in Bugis Village, Serangan Village, Denpasar, Bali. Data were obtained through direct observations, formal goat farmer in- terviews and key informant interviews that were conducted from April to July 2018. Two of the remaining three farmers who still kept rearing goats in Serangan Village were involved in this study. Each farmer housed his goats with a colony housing system and fed forages 10% of total body weight/day (control). One farmer supplemented ad- ditional feed of dwarf elephant grass (Pennisetum purpureum cv. Mott) silage (treatment). The variables observed: body weights, chest circumferences, body lengths, height of withers, and rump heights. This result showed that the body weight of 8 control goats was 30.67 ± 239 kg, which was significantly heavier than those of 29 treatment goats 20.65 ± 1.28 kg (P<0,05), however body weight of the treatment goats aged >5 years 38.73 ± 1.09 kg was significan- tly heavier than 33.33 ± 209 kg of those of the control goats (P<0.05). The highest correlation value in this result showed R2=0.964 between body weight and body length.